2016
DOI: 10.1590/s1517-707620160002.0043
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Titanium Doped Tungsten Disulfide Thin Films Produced via the Magnetron Co-Sputtering DC Technique

Abstract: In this work, titanium doped tungsten disulfide thin films (WS 2 -Ti) were deposited on AISI 304 stainlesssteel substrates using the magnetron co-sputtering DC technique. Films were produced with varying titaniumcathode power from 0 to 25 W. The titanium content of the WS 2 structure was determined using energy dispersive spectroscopy (EDS), thereby obtaining a maximum of 10% for the sample grown at 25 W. X-ray diffraction (XRD) results indicated, for the pure sample, the presence of a hexagonal phase of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…[30][31][32][33] Jhonattan et al deposited titanium doped tungsten disulfide film onto AISI 304 stainless-steel substrates using the magnetron co-sputtering DC technique. 34 Petr et al reported W-S-N coating deposited by d.c. reactive magnetron sputtering. They studied the effect of deposition conditions on chemical composition, morphology, tribological and mechanical properties.…”
mentioning
confidence: 99%
“…[30][31][32][33] Jhonattan et al deposited titanium doped tungsten disulfide film onto AISI 304 stainless-steel substrates using the magnetron co-sputtering DC technique. 34 Petr et al reported W-S-N coating deposited by d.c. reactive magnetron sputtering. They studied the effect of deposition conditions on chemical composition, morphology, tribological and mechanical properties.…”
mentioning
confidence: 99%
“…prepared WS 2 /Au and WS 2 /Cr composite films by magnetron sputtering, the results show that the doping of metal Au and Cr can improve the compactness of composite films, reduce the wear rate of composite films and improve their oxidation resistance. Jhonattan et al [8,9]. prepared WS 2 /Ti composite films by DC magnetron co-sputtering, the results confirm that the compactness and tribological properties of WS 2 /Ti composite films were improved, corrosion resistance was enhanced.…”
Section: Introductionmentioning
confidence: 73%